The physical self-concept across childhood: Measurement development and meaning for physical activity. (July 2022) - Dreiskämper, D; Tietjens, M; Schott, N
Abstract: The physical self-concept is considered a significant predictor of physical activity and persistence in childhood and youth. Based on Shavelson, Stanton, and Hubner's (1976) hierarchical structure of self-concept, several approaches have been developed to measure physical self-perception. A multi-dimensional fitness-based approach by Marsh (1990) shows a valid method for measuring physical self-concept in all age groups from 8 years old to adulthood. Furthermore, following standard childhood fitness test dimensions, instruments have been developed for middle to late childhood (Dreiskämper, Tietjens, Honemann, Naul, & Freund, 2015a ) and early childhood (Tietjens et al., 2018 ). However, based on Harter's (1980) approach of a more global and general skills-summarizing self-perception profile, other studies – preliminary coming from a motor development perspective – focused on measuring children's self-perception based on fundamental movement skills such as object control, locomotion, and stability. In this line, Estevan and Barnett (2018) proposed an adaption of Fox and Corbin's (1989) model. However, several research questions have remained unanswered because these different research directions have not been integrated yet: 1) How is the physical self-concept in childhood constructed, and how can it be measured? 2) How does the physical self-concept develop across childhood (and is this consistent with the assumptions about the self-concept as defined by Shavelson et al., 1976 )? And 3) What is the role of physical self-concept in behavior (i.e., PA) and its antecedents in childhood (and how)? The purpose of this discussion paper is to address these three more or less open questions from a self-concept research perspective. To this end, the models of Shavelson et al. (1976) and Marsh (1990) will be drawn upon to integrate the recent research developments into a new classification of the physical self-concept and its development throughout childhood. Highlights: This paper integrates the research from different perspectives on the development, structure, measurement and role for PA across childhood. By integrating different pathways of research, an adaption and extension of the physical self-concept model for childhood is presented. A proposal for a paradigm bringing the features of the self-concept (Shavelson et al., 1976 ) into a step-wise order. Theoretical assumptions on the meaning of skill and fitness perception are lead into a framework about the development and meaning of the physical self-concept across childhood. Implications for sport and exercise and research are derived based on the integration of the different existing research pathways, methods, instruments and empirical findings.